Outer-Membrane Penetration Barriers as Components of Intrinsic Resistance to Beta-Lactam and Other Antibiotics in Escherichia coli K-12 - Scudamore, R. Allan (1979)
A new technique has been devised to investigate the penetration of antibiotics through the gram-negative outer membrane; the application here was to study intrinsic resistance of Escherichia coli K-12. Exponential cells in broth were briefly treated with 2.5 mM ethylenediaminetetraacetic acid at 5°C to disrupt the outer membrane penetration barrier, and the response of treated and untreated cells to antibiotics was compared by turbidimetry. A barrier index was derived to describe the ability of 7 beta-lactam and 10 other antibiotics to penetrate the outer membrane of strain Y10. There was correlation between the molecular weight and log(10) barrier index (r = 0.59, P ≅ 0.01). The envelope mutant D22 (envA) had low barrier indexes for erythromycin, rifampin, ampicillin, and cloxacillin. For the beta-lactams, outer membrane penetration and affinity for inner membrane target site(s) triggering cell lysis were measured as independent components of the overall activity; although penetration and overall activity varied greatly, the affinities of most were within a narrow range.